Variation in nutrient use in ant assemblages along an extensive elevational gradient on Mt Kilimanjaro. (25th July 2014) - Peters, Marcell K.; Mayr, Antonia; Röder, Juliane; Sanders, Nathan J.; Steffan‐Dewenter, Ingolf; Parr, Kate
Abstract Aim We used the extensive climatic and land‐use gradient on Mt Kilimanjaro, Tanzania, to study large‐scale variation of nutrient use in ground‐foraging ant communities. In particular, we tested the hypothesis that recruitment of ants to six different nutrients would vary with elevation and between land‐use regimes. We also tested whether the nutrient space (number and evenness of nutrients) used by ants decreases as species richness declines with elevation, a pattern expected because of complementarity in nutritional intake of species. Location Mt Kilimanjaro, Tanzania. Methods Standardized bait experiments with six nutrient treatments [carbohydrates (CHO), amino acid, CHO–amino acid mix, NaCl, H2O and lipids] were performed at a total of 48 study sites in natural and managed ecosystems along an elevational gradient from 860 to 4390 m a.s.l. We used generalized linear models, information theory‐based model inference and null model analyses to test hypotheses. Results The species richness of ant communities declined with elevation in natural ecosystems but peaked at mid‐elevations in managed ecosystems. We found that the use of four nutrients (NaCl, CHO, H2O and lipids) varied with elevation and, in the case of NaCl and H2O, with land use. Use of H2O and CHO decreased with elevation, while lipid use increased. NaCl use increased with elevation in natural ecosystems but decreased in managed ecosystems. The nutrient space exploited by ant communities increased with ant species richness in natural ecosystems but decreased slightly in managed ecosystems. The difference could be because there are more trophic generalists in managed ecosystems and more specialists with complementary foraging niches in natural ecosystems. Main conclusions Ant communities in different environments appear to be limited by different types and numbers of nutrients. This spatial heterogeneity in nutritional ecology is probably determined by both the environmental availability of nutrients and the functional composition of ant communities.